Selection of Unployed Aircraft for Training of Small-Range Aircraft Defense System AHP – TOPSIS Optimization Methods - Đukić, Đorđe Nikola; Petrović, Ivan; Božanić, Darko; Delibašić, Boris (Yugoslav Journal of Operations Research; Vol 32 No 3 (2022)DO - 10.2298/YJOR211125007D, 2022)
The article solves the problem of more efficient and economical training of combat crews on short range air defense systems. The training so far is based on the use of conventional means, which require the engagement of a large number of people, expensive equipment, long-term planning and spending a lot of time and space. The use of unmanned aerial vehicles - drones, greatly saves all these resources. The mathematical model, using the methods of multicriteria decision-making - Analytical Hierarchical Processes (AHP) and optimization - The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), will determine the weighting coefficients and then ranking alternatives for drone selection, which would replace classical means for training and coaching, which would meet all the parameters and characteristics of the training itself and training equipment. The methods will first prioritize the selection criteria, and then, based on their importance, concretize the solution among the offered alternatives.